Photoelectrode FTO/ Anodized TiO2 Production and Characterization for Methylene Blue Affected Photoelectrochemical Decomposition - Caliskan, Berrak; Şayan, Enes; Kiziltas, Hakan (Recent Innovations in Chemical Engineering, 2024)
Background: The production of thin film TiO2 nanostructured systems for electrocatalytic, photocatalytic, and photoelectrocatalytic applications has been an essential topic in recent years. Due to the light-sensitive effect of TiO2, it can be produced by various methods and used as a photoelectrode to remove dye. Using magnetron sputtering, Ti thin films can be deposited on different substrates and converted into transparent TiO2 structures by electrochemical anodization. Methods: In this study, the thin Ti film was produced using a magnetic spraying technique on the FTO substrate, and then an anodic TiO2 structure was obtained by the anodization technique. TiO2 films produced by the anodizing technique were used as a photoelectrode for the degradation of MB. The reactor contained 400 mL of 20 mg/L MB solution at 20 °C. The produced photoelectrode was characterized by the SEM/EDS, FTIR, XRD, and UV-Vis Spectrophotometer analyses. Results: The EDS analysis confirmed the presence of titanium and oxygen in the FTO/ Anodized TiO2 photoelectrode. The XRD results showed that all the peaks of the produced FTO/ Anodic TiO2 were associated with the anatase phase of TiO2. According to the FTIR spectroscopy, the functional groups of the anodized TiO2 were obtained for the FTO/ Anodized TiO2. The electrocatalytic, photocatalytic, and photoelectrocatalytic degradation experiments were performed with the degradation of the dye solution of MB on the FTO/ Anodic TiO2 photoelectrode, and the rates of dye degradation were determined as 17.12%, 64.67%, and 82.12%, respectively. Conclusion: This study showed that the methylene blue dye of FTO/ Anodic TiO2 is a suitable photoelectrode for electrocatalytic, photocatalytic, and photoelectrocatalytic degradation.
Keywords: FTO